KAJIAN TEKNIS PEMANFAATAN ABU TERBANG (FLY ASH) UNTUK PT. MAKMUR SEJAHTERA WISESA SEBAGAI BASE LAYDOWN ASET PROJECT PT. ADARO INDONESIA - Dedi Herawadi; Edy Nursanto; Eddy Winarno (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2016)
Utilization coal an energy source to produce electricity and coal wastes such as fly ash, estimated at 7 thousand tons of fly ash annually in power plant PT. Makmur Sejahtera Wisesa (PT.MSW). One attempt utilizing waste fly ash is as a compound to increase the carrying capacity of clay. Pit Wara, clay mining is not entirely good and meet the technical criteria as a constituent material for pavement. Because clay should be improved or stabilized. In general, this problem is resolved by making clay material from other locations, this will result increased operating costs. This research aimed at obtaining the compressive strength of clay that fits the criteria of technical base in the manufacturing base of laydown in the Pit Wara to improve soil properties of clay in the form of stabilization by adding fly ash it is called stabilizing agent (Hartosukma, E.W, 2005). The research methodology used material sample in the Pit Wara and power plant PT.MSW, to be tested in the laboratory. Compacting (Compaction test) and CBR, unknown effect of adding fly ash to the value optimum moisture content (OMC), the value of moisture dry density of clay and material mix. The test results showed that the addition of 10% fly ash can be increase the value of CBR to 16 (Criteria for subgrade CBR that category as well) when compacted at the optimum water content of 17.5%. The decline in value of the compressive strength of the material mixture (clay and fly ash) when done excessively the addition of fly ash is the addition of 20% fly ash is not linear.